If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -3 = 2y + 12 Reorder the terms: -3 + -5y = 2y + 12 Reorder the terms: -3 + -5y = 12 + 2y Solving -3 + -5y = 12 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -3 + -5y + -2y = 12 + 2y + -2y Combine like terms: -5y + -2y = -7y -3 + -7y = 12 + 2y + -2y Combine like terms: 2y + -2y = 0 -3 + -7y = 12 + 0 -3 + -7y = 12 Add '3' to each side of the equation. -3 + 3 + -7y = 12 + 3 Combine like terms: -3 + 3 = 0 0 + -7y = 12 + 3 -7y = 12 + 3 Combine like terms: 12 + 3 = 15 -7y = 15 Divide each side by '-7'. y = -2.142857143 Simplifying y = -2.142857143
| 0.005669x^4+0x^3+0x^2-5x+858.468=0 | | 3x/5-3=21 | | -6-1x+12x=10x+6 | | 5x+11y=6x+3y | | 2x+5=8x-4 | | Abx^2-(a+b)x+1=0 | | 10(x-2)=12 | | 10(e-2)=12 | | 10(0-2)=12 | | 10+N+N=18 | | b=351655c-1x-1 | | 351655=bxc | | (5X+6)-(-3x+10)=2x-4 | | 3(x+3)-7=4(x-2)+5 | | 6(x+13)=7x-8-3x | | 0.009x+0.2(500-x)=0.03*500 | | 3Y-2Z=-5 | | 4[x-1]=0 | | sin(3pix)=1 | | 3x(1+x)=0 | | 5x*2-7x-24=0 | | (x-3)(x-5)=64 | | (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 | | 3*x-x*log(x)=log(e^5) | | 3x-xln(x)=lne^5 | | 5x-7x-24=0 | | 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 |